Rhythm & cues: circadian clock genes and temporal reproductive isolation in the European corn borer moth (Ostrinia nubilalis). - Levy, Rebecca. (2017)
Abstract: Temporal reproductive isolation is currently a well-documented but poorly-understood mechanism for divergence between incipient species. The circadian clock regulates biological rhythms on 24-hour cycles and is potentially involved in detection of seasonal variation in photoperiod, and genes in this pathway are prime candidates for genetic control of both seasonal and circadian shifts in mating time. The European corn borer, Ostrinia nubilalis, is a model for how temporal isolation contributes to speciation, as the species' E and Z pheromone strains are temporally isolated from each other on seasonal and 24-hour time scales. In this thesis, I examine how genetic variation within the O. nubilalis clock is linked to life cycle timing in the Z strain and shifts in generation number across a latitudinal cline, and how key circadian genes are differentially expressed between the strains during scotophase, which may be triggering divergence in the timing of pheromone release and subsequent mating.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biology.; Advisor: Erik Dopman.; Committee: Elizabeth Crone, and Mitch McVey.; Keywords: Biology, Genetics, and Evolution & development.